Congestive cardiac failure: central role of the arterial blood pressure. Issue 3 (September 1987) - Harris, P
Abstract : A review of the history of our knowledge and understanding of the peripheral oedema of congestive cardiac failure points to the conclusion that an inability of the heart to maintain the arterial pressure is of central importance in this condition. Although the function of the circulation is to perfuse the tissues, the body monitors the adequacy of its perfusion, not not through metabolic messengers carried from the tissues in the blood stream, but by sensing the arterial pressure; and the mechanisms evoked act to maintain the arterial pressure. In the short term this is achieved by autonomic regulation of the heart and blood vessels; in the longer term the arterial pressure is maintained through an increase in the blood volume by a retention of salt and water by the kidney. To support the latter process, intrinsic renal mechanisms are successively magnified by the renin-angiotensin-aldosterone system and by the activities of the sympathetic system and vasopressin. The natriuretic influence mediated through volume receptors and the release of atrial peptide is overruled by the arterial baroreceptors, so that the body maintains the arterial pressure at the expense of an increase in blood volume. In these ways the syndrome of congestive cardiac failure may be regarded as one which arises when the heart becomes chronically unable to maintain an appropriate arterial pressure without support.